Modelling of background water quality for calculation of dump specifications - Білогуров, Віктор Петрович; Нагорна, Ганна Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2012)
The paper purpose is a method development for definition of background water pollutants concentration, which are necessary for limitation of waste water